Where do older adults die in Brazil? An analysis of two decades - Kenny Regina Lehmann; Dyayne Carla Banovski; Bruna Fernandes; Dagna Karen de Oliveira; Sadana Hillary Dal'Negro; Ana Carolina de Campos (Brazilian Society of Geriatrics and Gerontology, 2022)
Objective: To describe the characteristics of older adult deaths reported in Brazil between 1998 and 2018. Methods: This is a retrospective, descriptive study performed using secondary data from the Brazilian Ministry of Health. Results: During the analyzed period, 14 145 686 older adults died in the country, of which 40.42% were over 80 years old. The main cause of death was circulatory system disease (21.50%), and the most frequent place of death was a hospital environment (68%). The Southeast region accounted for 52.83% of the country's hospital deaths and 73.33% of those occurring in other health facilities, whereas 38.56% of the deaths that happened at home took place in the Northeast region. Conclusions: The hospital environment was the predominant place of death in all regions of the country, and the main causes of death were chronic noncommunicable diseases. Alternative care modalities emerge as a possibility of establishing accessible end-of-life care in scenarios other than the hospital.